IMPACT OF CORPORATE GOVERNANCE ON PERFORMANCE OF BANKS IN INDIA (IITM JOURNAL OF BUSINESS STUDIES (JBS), 2024)
The study explores the intricate relationship  between corporate governance mechanisms  and their influence on the performance metrics  of banks, considering different ownership  structures in the Indian banking sector. In  light of the economic reforms and heightened  regulatory scrutiny post the 1990s, this study  investigates whether the changes in governance  practices have substantially affected the  performance outcomes of banks in terms of  profitability, risk management, and operational  efficiency.
Keywords: Performance Metrics; Ownership Structures; Emerging Market Banking Systems